Evidence for a Robertsonian fusion in Solea senegalensis (Kaup, 1858) revealed by zoo-FISH and comparative genome analysis - Aglaya García-Angulo; Manuel A. Merlo; Silvia Portela-Bens; María E. Rodríguez; Emilio García; Ahmed Al-Rikabi; Thomas Liehr; Laureana Rebordinos (BMC Genomics, 2018)
Abstract Background Solea senegalensis (Kaup, 1858) is a commercially important flatfish species, belonging to the Pleuronectiformes order. The taxonomy of this group has long been controversial, and the karyotype of the order presents a high degree of variability in diploid number, derived from chromosomal rearrangements such as Robertsonian fusions. Previously it has been proposed that the large metacentric chromosome of S. senegalensis arises from this kind of chromosome rearrangement and that this is a proto-sex chromosome. Results In this work, the Robertsonian origin of the large metacentric chromosome of S. senegalensis has been tested by the Zoo-FISH technique applied to two species of the Soleidae family (Dicologlossa cuneata and Dagetichthys lusitanica), and by comparative genome analysis with Cynoglossus semilaevis. From the karyotypic analysis we were able to determine a chromosome complement comprising 2n = 50 (FN = 54) in D. cuneata and 2n = 42 (FN = 50) in D. lusitanica. The large metacentric painting probe gave consistent signals in four acrocentric chromosomes of the two Soleidae species; and the genome analysis proved a common origin with four chromosome pairs of C. semilaevis. As a result of the genomic analysis, up to 61 genes were annotated within the thirteen Bacterial Artificial Chromosome clones analysed. Conclusions These results confirm that the large metacentric chromosome of S. senegalensis originated from a Robertsonian fusion and provide new data about the chromosome evolution of S. senegalensis in particular, and of Pleuronectiformes in general.